2006
DOI: 10.1111/j.1365-2524.2006.00684.x
|View full text |Cite
|
Sign up to set email alerts
|

Equine-assisted psychotherapy: a mental health promotion/intervention modality for children who have experienced intra-family violence

Abstract: Equine-assisted psychotherapy (EAP) is a specialized form of psychotherapy using the horse as a therapeutic tool. This modality is designed to address self-esteem and personal confidence, communication and interpersonal effectiveness, trust, boundaries and limit-setting, and group cohesion. Substantial numbers of children witness family violence. There is evidence that violence between parents has adverse effects on the children in the family. These children are at greater risk of behavioural problems and ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
121
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(130 citation statements)
references
References 27 publications
(30 reference statements)
4
121
0
4
Order By: Relevance
“…In conclusion, this work poses the basis for the application of novel high level signal processing techniques for stationary and non-stationary signals [113,114], already used in investigating human-to-human interaction [115][116][117], to animals, and particularly to horses, in order to objectively reveal interesting responses of both the central and autonomic nervous system (ANS) for a particular uncommon stimulation. Moreover, the achieved results lead us to conclude that a quantitative measure of the human-horse interaction is viable, and it could be very effective in many fields of application, for example in therapy assisted by equine (EAT) [2,118] or for controlling the effect of therapeutic horseback riding [119]. In this field, our paradigm could permit analyzing the emotional interaction of a human patient with a "standardized horse" (a horse specifically trained and managed to create a controlled positive emotional background with a human).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In conclusion, this work poses the basis for the application of novel high level signal processing techniques for stationary and non-stationary signals [113,114], already used in investigating human-to-human interaction [115][116][117], to animals, and particularly to horses, in order to objectively reveal interesting responses of both the central and autonomic nervous system (ANS) for a particular uncommon stimulation. Moreover, the achieved results lead us to conclude that a quantitative measure of the human-horse interaction is viable, and it could be very effective in many fields of application, for example in therapy assisted by equine (EAT) [2,118] or for controlling the effect of therapeutic horseback riding [119]. In this field, our paradigm could permit analyzing the emotional interaction of a human patient with a "standardized horse" (a horse specifically trained and managed to create a controlled positive emotional background with a human).…”
Section: Discussionmentioning
confidence: 92%
“…This was guided by the strong empirical evidence of the positive outcomes in equine assisted therapy (EAT) and horseback riding in therapeutic programs [1], as well as the positive impact of animal companionship on human quality of life [2], where the equine is an important element of these therapeutic practices, with its feelings and behavior. For this purpose, the investigation of the modality in which both human and horse can communicate might be crucial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a detailed case study including 24 and later 20 subjects (Taylor et al, 2009) as well as in the study of Kern et al (2011) the long-term positive effects of HT in autistic subjects were described. Schultz, Remick-Barlow and Robbins (2007) monitored 63 children, who were witnesses or victims of domestic violence. After 19 HT sessions a more distinct effect on those who were victims of domestic violence, abuse or negligence was observed.…”
Section: The Effect Of Ht Interventionmentioning
confidence: 99%
“…The disorders for which efficacy has been suggested include depression, childhood internalizing behaviors, and low self-esteem [1][2][3][4][5]; anxiety [6][7][8]; grief and loss [9]; attention-deficit/hyperactivity disorder [10]; conduct and antisocial personality disorders and childhood externalizing behaviors [5,11,12]; dissociative disorders [13]; post-traumatic stress disorder [14][15][16]; Alzheimers disease and dementia [17][18][19][20]; pervasive developmental disorders and learning disabilities [21][22][23][24][25]; chronic mental illnesses [26][27][28][29][30][31]; and general psychological distress among residential treatment center patients [32,33] conducted a comprehensive meta-analysis of studies involving animal-assisted therapy. They concluded that animal-assisted therapy was associated with moderate effect sizes in improving outcomes in four areas: autism-spectrum symptoms, medical difficulties, behavioral problems, and emotional well-being.…”
Section: Introductionmentioning
confidence: 99%